Vortex Flow‐controlled Circularly Polarized Luminescence of Achiral Pt(II) Complex Aggregates Assembled at the Air‐Water Interface (Small Methods 12/2022). Issue 12 (13th December 2022) - Maeda, Takatoshi; Mori, Taizo; Ikeshita, Masahiro; Ma, Shing Cho; Muller, Gilles; Ariga, Katsuhiko; Naota, Takeshi
Abstract : Inside Back Cover In article number 2200936, Mori, Muller, Ariga, Naota, and co‐workers present a highly facile and precise controlling method of the circularly polarized luminescence of the achiral trans‐bis(salicylaldiminato)Pt(II) complex by specific aggregation under clockwise and counterclockwise vortex conditions with various flow rates at an air‐water interface.